Distribution of Radial Root Position of Maxillary Central Incisors on Cone Beam Computerized Tomography : Radial Root Position of Maxillary Incisors - Danyal, Ahmad; Khaliq, Mehreen; Ahmad, Taif; Haseeb, Muhammad; Khan, Zubair Ahmad; Maqbool, Maha; Manzoor, Usman; Ataullah, Khurram (Pakistan Journal of Health Sciences, 2025)
Knowledge about the radial root position before possible replacement of central incisors for immediate implant is of pivotal importance to clinician. It varies among different populations. Objective: To determine distribution of radial/sagittal root position in maxillary central incisors in patients reporting to 2 tertiary care hospitals of Lahore, Pakistan using CBCT. Methods: Sample size of 110 individuals between 20-50 years, strictly falling in inclusion criteria was used. Cross sectional study with non-probability consecutive sampling technique was applied in Department of Periodontology at Fatima Memorial Hospital and University college of Medicine and Dentistry, from Jan 2023 to Sep 2023. The position of maxillary central incisor roots was determined using CBCT. Chi-square test was used for stratification based on age and gender. Results: The mean age was 33.67 ± 8.68 and sample consisted of females 50 (45.45%) and males 60 (54.55%). The most common root position was class I, 79 (71.82%), followed by class II, 20 (18.18%), then class IV, 7 (6.36%) and least was class III, 4 (3.64%). The difference among genders (p=0.272) and age (p=0.161) were insignificant statistically. Conclusions: Most common incidence of radial root spatial position for maxillary central incisor is buccal (class 1), followed by II (middle) but class IV and III also existed and must analyzed CBCT to determine the radial root position before any immediate implant in esthetic zone for optimal esthetic and functional outcome.